Endoscopic transluminal interventions and percutaneous drainage in acute infected necrotizing pancreatitis: experience of a specialized center - Susak, Y. M.; Puzyr, N. V. (General Surgery, 2025)
Acute infected necrotizing pancreatitis is a life‑threatening complication. Over the past 25 years, the introduction of minimally invasive techniques has significantly improved treatment outcomes. However, variations in disease progression, anatomical characteristics, and the need for optimal personalized invasive strategies remain subjects of ongoing debate. Objective – to evaluate and compare the treatment outcomes of acute infected necrotizing pancreatitis with peripancreatic and combined (parenchymal + peripancreatic) lesions, using endoscopic transluminal interventions versus the traditional «step-up» approach. Materials and methods. A retrospective study involving 67 patients (mean age – 50.5±10.9 years) was conducted from 2021 to 2024. Group 1 (n=28) underwent endoscopic transluminal interventions (ETI), including endoscopic necrosectomy when necessary, while Group 2 (n=39) was treated using the traditional “step‑up” approach, which involved percutaneous drainage (PD) and open necrosectomy if indicated. There were no significant differences between the groups in baseline characteristics or in the size of the walled-off pancreatic necrosis (WON). Clinical success was categorized as complete, partial, or absent. Statistical analysis was performed using χ2 and the Mann‑Whitney U test. Results. The ETI group required fewer repeat procedures: a single procedure was sufficient for 50% of patients in Group 1, whereas in Group 2, the majority of patients needed ≥3 procedures (p=0.013). Complete clinical success was achieved in 64.3% of patients in Group 1, compared to only 25.6% in Group 2 (p=0.004). External pancreatic fistulas occurred only after PD (12.8%, p=0.049). The mortality rate in the ETI group was lower (10.7% vs. 23.1%), although this difference was not statistically significant (p=0.193). Additionally, Group 1 had a shorter average hospital stay (56.2±27.2 days) compared to Group 2 (63.4±23.7 days). Conclusions. Endoscopic transluminal interventions within a multidisciplinary “step‑up” approach are safer and more effective than isolated percutaneous drainage. ETI reduce the need for repeat interventions, lower the incidence of complications, and contribute to improved clinical outcomes in cases of acute infected necrotizing pancreatitis. PD and ETI are not mutually exclusive and can be incorporated into hybrid treatment strategies.